Analysis of Women’s Empathetic Agreement -Making Skill by their Husbands: a Sample of Grounded Theory - Ghasemi Dehnavi, Tayebeh; Yousefi, Zahra; Farhadi, Hadi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Today, maintaining a family not only requires knowledge but also requires its own skills. One of the skills can be empathetic agreement that it can be reached by men. The goal of present study was to analysis of empathetic agreement-making skills among married women by their husbands. Methods: This study was conducted using the social structuralism perspective method developed by Charms (2014). The study population included all married men who had succeeded in having happy and stable families and the sample consisted of 10 of these men who were purposefully selected from a homogeneous type based on entry and exit criteria. The research tool was a semi-structured interview. The duration of each interview was between 60 and 120 minutes. The data collected by Charms (2014) method were analyzed in three stages of initial coding, axial coding and final classification. Findings: The findings revealed three dimensions to the grounded theory: (1) what empathetic agreement- making is, (2) why empathetic agreement-making, and (3) how empathetic agreement-making. Conclusion: This grounded theory can be effective in facilitating family education for the success of men in married life, studies related to empathetic agreement-making and facilitating empathetic agreement-making in the field of family counseling and treatment, and divorce prevention.